Global Banking Industry Financials : An Analysis of Derivative Usage on The Financial Performance of Major Banks - Syahwildan, Muhamad; Latif, Abdul; Widiastuti, Widiastuti (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
Hedging has become a vital strategy for the banking sector, given the complexity and volatility of today's global financial markets. Hedging is also used as one of the strategies to reduce risks associated with fluctuations in the value of assets and liabilities. In Indonesia, the Banking Sector faces challenges in managing risks associated with economic and financial variability. This study focuses on micro and macro factors that can influence hedging decisions in the banking sector. The micro factors considered in this study are liquidity and leverage. On the other hand, the macro factors considered in this study are interest rates and exchange rates. The sampling method used is nonprobability sampling, namely the purposive sampling method. The samples in this study were 15 banking sector companies listed on the IDX for the period 2020-2023. This study uses the help of Eviews 12 used to test the goodness of the model, and logistic regression and hypothesis relationships designed in this study. The findings in this study indicate that interest rates have a negative and significant impact on hedging decisions, and liquidity has no significant effect on hedging decisions. This can happen because market liquidity is stable and not volatile, while exchange rates and leverage positively and significantly affect hedging decisions.